Living with the Virus: Graduate School Students Evaluation of Stressors Related to the Pandemic - Geronimo, Jessica Frey Shane S.; Morada, Charmaine M.; Reyes, Joseph Niño A.; Zapanta-Ribu, Mary Shaira Christa; Vigonte, Florinda G.; Malang, Bernandino P.; Abante, Marmelo V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The Coronavirus Disease (COVID-19) becomes a global threat in March of 2020. Several countries were on lockdown. It affects health and results in post-traumatic stress disorder (PTSD). During the quarantine and lockdown, the lack of freedom resulted to psychological consequences. In the Philippines, it was March 15, 2020 when the initial COVID-19 was instituted commonly recalled due to lockdown and canceled classes. Filipinos in general and students in particular were worried of their health information including vaccine availability, efficacy, and infection rates. Mental health is impaired by pandemic risks. UNICEF Philippines, then, advocated alternative and continuing learning. The major purpose of this research is to determine graduate students' levels of stress during the COVID-19 outbreak. The descriptive-correlational design was used for the quantitative investigation. The 150 responders are selected at random from Metro Manila master's degree students in the academic year 2022-2023. The adopted questionnaire consists of seven items that are multidimensional scales with psychometric qualities. Using chi-square, the findings revealed that, among demographic profiles, only age showed a significant relationship with the association of global stress. Thus, it can be stated that age is a crucial factor in assessing the global stress of graduate students. COVID-19 is more contagious in adults, reflecting their anxiety and stress during the epidemic.